Screen Time: Artistic Networked Chronotopes - Lourie, Anitra (Sens public, 2024)
This article examines contemporary artists’ appropriation of social media platforms to explore new narrative forms. In addition to the aesthetic and thematic qualities of these works, artists’ social media narratives reveal pragmatic and discursive qualities, notably unique space-time configurations. Artists such as Molly Soda, Amalia Ulman, Martine Gutierrez, or even the design team Brud’s Instagram CGI character Lil Miquela, highlight the temporal and spatial narrative dimensions of social media designs and the ways these platforms facilitate, guide, and frame self-representation and storytelling. This article will explore the ways in which narrative elements are both integrated into the design of social media platforms and reappropriated artistically for critical or reflexive use, (re)constructing the intentions and potentials of both the technology and the narrative concepts. This reflection draws on literary discourse theory as well as digital narratology and socio-linguistics, specifically employing French philosopher Paul Ricœur’s concept of narrative identity and emplotment as well as Russian structuralist Mikhail Bakhtin’s theory of chronotope (Greek for “time-space”). Through this analysis, we interpret artistic social media practices as self-narratives that employ medium-specific temporal configurations and challenge the traditional narrative framework.